THE EFFECTIVENESS OF “TATWIRUL LUGHOH PROGRAM” IN IMPROVING ORAL COMMUNICATION SKILL - luqman hadi (Graduate Program, University of Islam Malang, 2020)
Tatwirul lughoh program that is designed to improve foreign language speaking. The program has became the spirit where all students must use two languages, English and Arabic. The purpose of the tatwirul lughoh is to support education and to form a person who are understand and good at speaking foreign languages. 24 hours a day santri uses foreign language to interact directly with their friends, for example Arabic and English which are scheduled alternately in each week. So in one week the students are required to use English,This study was experimental research design to examine the degree of between pretest and postest towards students’ oral communication skill. The population of this study was students of MA Al Amanah Bilingual Sidoarjo, which were 12 students as the samples. It was a qualitative and quantitative research. The instruments were a speaking test and questionnaires.The result of the statistical analysis shows that the effectiveness between pretest and postest simultaneously towards speaking is calculated with the T-test is 14.4166, It means that there is a significant improvement between before and after joining the Tatwirul Lughoh program in oral communication skill. That way, the treatment in Tatwirul Lughoh program is succesfully running well, because it can make an improvement to the students in oral communication skill, it can be concluded that the mean of pretest is 39.9167 and posttest is 54.3333. In addition the teaching material and the teaching strategy are the supporting factor to improve the students in oral communication skill.Based on the findings of this study, several suggestions are addressed for English teachers and future researchers. For the teachers, they can help students to explore their ability in learning English particularly speaking skill. For future researchers, who want to conduct the similar topic, might include qualitative data, such as the result of interview with teacher or students to know what program language that can make improve their oral communication skill and how it managed. In elaborating with quantitative data, the future researchers could use the experimental research design to know how the effectiveness of the language program treatment itself especially in oral communication skill.Key Words : Tatwirul Lughoh, Oral Communication, Perception.